2018
DOI: 10.1080/09638288.2018.1424949
|View full text |Cite
|
Sign up to set email alerts
|

Living with a disability: a qualitative study of associations between social relations, social participation and quality of life

Abstract: Across disabilities, caregiving, dependency, understanding and acceptance, and discrimination and prejudice were all important aspects for the quality of life of the individuals. Social relations were closely related to social participation, and the latter affected the quality of life of the participants. Social tactics were used to navigate social relations. Implications for rehabilitation We suggest to formalize the concept of social tactics and use it in patient education to enhance quality of life in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…In adolescence, social relations become important. For proper social development, it is necessary to make friends of different ages and genders, participate in social activities, and join friend groups (Jespersen et al, 2019 ). Problems such as difficulties in making friends, shyness in relationships with the opposite sex, and the inability to express emotions might be experienced intensely in adolescence (Nesi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In adolescence, social relations become important. For proper social development, it is necessary to make friends of different ages and genders, participate in social activities, and join friend groups (Jespersen et al, 2019 ). Problems such as difficulties in making friends, shyness in relationships with the opposite sex, and the inability to express emotions might be experienced intensely in adolescence (Nesi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To have support, but also help from family and friends, is considered the main core for gaining quality of life ( 20 ). We found that only one in eight people in our study had a partner (12.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in findings can perhaps be explained by their smaller sample size, slightly different outcomes, and analyses of data. The link between the quality of life and social relations (family, friends, and others), affects an individual's life, both positively and negatively depending on the characteristic of the relationship ( 20 ). Our findings also reinforce the crucial need for good communication abilities, particularly important for social functioning in young adults with CP ( 6 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 External observers estimating the quality of life of persons with disabilities tend to vastly underestimate relative to estimations reported by those with disability themselves, who tend to endorse good or excellent quality of life. [16][17][18][19] These tendencies might stem from misguided preconceptions of lower life or hedonic value. In acute settings, parallel preconceptions might result in premature withdrawal of care or withholding of life-saving treatments for patients with disabilities, often stemming from covert or overt beliefs that disabled lives are not worth living and therefore not worth saving.…”
Section: The Heavy Weight Of Biasmentioning
confidence: 99%